(untitled) (The International Research Journal of Management Science, 2018)
The purpose of this paper is to examine the relationship between firm strategy and bankruptcy risk. The research design consists of descriptive and causal-comparative research designs in order to deal with the various issues raised in this study. In addition, this paper uses the Altman-Z score which combines several measures of performance and risk to come up with a score that denotes the bankruptcy risk inherent in a firm. Secondary data has been used collected from annual audit report of concerned organization of manufacturing and hotel industries from fiscal year 2000/01 to 2014/15. Factor analysis, descriptive statistics, correlation analysis, and regression analysis are different statistical tools that have been used for this study. Further, cost leadership and differentiation strategies has been constructed from selling, general, and administrative expenses scaled by net sales; net sales scaled by cost of goods sold; net sales scaled by net book value of plant and equipment; and net sales scaled by net book value of plant and equipment variables through factor analysis. By regressing Altman-Z score against relevant control variables and proxies for differentiation and cost leadership strategies, this study has evaluated the relationship between bankruptcy risk and firm strategy. The analysis shows that the enterprises adopting higher selling, general and administrative expenses in association with higher gross profit margin have been pursuing differentiation strategy whereas higher investment on property, plant and equipment along with their existing value indicates that they have been following cost leadership strategy. Value of Nepalese enterprises pursuing cost leadership strategy has a positive effect on reducing bankruptcy risk while pursuing differentiation strategy has a negative effect on reducing bankruptcy risk.